Comparative assessment of climate change and its impacts on three coastal aquifers in the Mediterranean - Stigter, T. Y.
A comparative study on climate change and its impacts on coastal aquifers is performed for three Mediterranean areas. Common climate scenarios are developed for these areas using the ENSEMBLES projections that consider the A1b scenario. Temperature and precipitation data of three climate models are bias corrected with two different methods for a historic reference period, after which scenarios are created for 2020–2050 and 2069–2099 and used to calculate aquifer recharge for these periods based on two soil water budget methods. These multiple combinations of models and methods allow incorporating a level of uncertainty into the results. Groundwater flow models are developed for the three sites and then used to integrate future scenarios for three different parameters: (1) recharge, (2) crop water demand, and (3) sea level rise. Short-term predictions are marked by large ranges of predicted changes in recharge, only showing a consistent decrease at the Spanish site (mean 23 %), particularly due to a reduction in autumn rainfall. The latter is also expected to occur at the Portuguese site, resulting in a longer dry period. More frequent droughts are predicted at the Portuguese and Moroccan sites, but cannot be proven for the Spanish site. Toward the end of the century, results indicate a significant decrease (mean [25 %) in recharge in all areas, though most pronounced at the Portuguese site in absolute terms (mean 134 mm/year) and the Moroccan site in relative terms (mean 47 %). The models further predict a steady increase in crop water demand, causing 15–20 % additional evapotranspiration until 2100. Scenario modeling of groundwater flow shows its response to the predicted decreases in recharge and increases in pumping rates, with strongly reduced outflow into the coastal wetlands, whereas changes due to sea level rise are negligible.